2008
DOI: 10.2967/jnumed.108.055806
|View full text |Cite
|
Sign up to set email alerts
|

Does 18F-FDG PET/CT Improve the Detection of Posttreatment Recurrence of Head and Neck Squamous Cell Carcinoma in Patients Negative for Disease on Clinical Follow-up?

Abstract: Posttreatment surveillance for the recurrence of head and neck squamous cell carcinoma (HNSCC) is a diagnostic challenge. Tissue distortion from radiation and surgery can obscure early detection of recurrence by conventional follow-up approaches such as physical examination, CT, and MRI. Several studies have shown that 18 F-FDG PET may be an effective technique for the detection of persistent, recurrent, and distant metastatic HNSCC after treatment. The aim of this prospective study was to determine the benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
198
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(209 citation statements)
references
References 23 publications
3
198
1
7
Order By: Relevance
“…PET 1 and 2 detected malignancy in 16 of the 18 patients and thus, 18 F-FDG PET performed at 3-6 mo after therapy, in accordance with the findings of a retrospective study by Lee et al (26), was the best timing for imaging after treatment. In 2 studies, systematic 18 F-FDG PET/CT showed a high accuracy at 12 mo after treatment (27,28). However, the authors suggested a higher impact of 18 F-FDG PET at 6 mo after treatment, because the 18 F-FDG PET at 12 mo after treatment had significantly less impact than did earlier performed 18 F-FDG PET motivated by clinical suspicion (27).…”
Section: Discussionmentioning
confidence: 81%
“…PET 1 and 2 detected malignancy in 16 of the 18 patients and thus, 18 F-FDG PET performed at 3-6 mo after therapy, in accordance with the findings of a retrospective study by Lee et al (26), was the best timing for imaging after treatment. In 2 studies, systematic 18 F-FDG PET/CT showed a high accuracy at 12 mo after treatment (27,28). However, the authors suggested a higher impact of 18 F-FDG PET at 6 mo after treatment, because the 18 F-FDG PET at 12 mo after treatment had significantly less impact than did earlier performed 18 F-FDG PET motivated by clinical suspicion (27).…”
Section: Discussionmentioning
confidence: 81%
“…Treatment with radiotherapy and surgery causes inflammation, scarring, and tissue distortion, which can limit the interpretation of anatomic imaging techniques such as CT and MR imaging (9,10). In contrast, the metabolic information provided by 18 F-FDG PET/CT allows it to serve as an effective tool for detecting recurrence, regional lymphatic spread, and distant metastases (11).…”
mentioning
confidence: 99%
“…The value of follow-up PET/CT for patient outcome, and the added value to the clinical assessment, are not fully established. Previous studies (11,(19)(20)(21) have shown the prognostic significance of follow-up PET or PET/CT performed within 1 y after the completion of therapy. A recent study demonstrated the temporal patterns of HNSCC recurrence with 18 F-FDG PET/CT and concluded that PET/CT detected 73 asymptomatic recurrences in 110 patients with recurrence, with 95% of the observed recurrences being detected within 24 mo (22).…”
mentioning
confidence: 99%
“…The role of 18 F-FDG PET or 18 F-FDG PET/CT for the early detection of recurrent disease is addressed elsewhere (3,5,6).…”
Section: Identification Of Radiotherapy Targets Based On 18 F-fdg Petmentioning
confidence: 99%